2020
DOI: 10.1016/j.jor.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications and causes of 30- and 90-day readmission after direct anterior approach primary total hip arthroplasty

Abstract: We aimed to report causes of readmission 30 and 90 days following a total hip arthroplasty (THA) using the direct anterior approach (DAA). Methods: Three hundred and two patients (335 hips) underwent a DAA-THA for primary osteoarthritis. Results: The main reasons for 30 and 90-day readmission were wound related problems, dislocation (rate: 0.9%) and deep infection. The readmission rates at 30 and 90 days were 1.8% and 2.7%, respectively. Age over 60 years and morbidly obese patients were at risk for complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Some authors [ 15 , 18 ] reported that patients with obesity and advanced age were not suitable for DAA THA, and the risk of complications such as fracture was high. In this study, the patient BMI was heterogeneous, and the continuity analysis did not show that BMI had a significant effect on the incidence of fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors [ 15 , 18 ] reported that patients with obesity and advanced age were not suitable for DAA THA, and the risk of complications such as fracture was high. In this study, the patient BMI was heterogeneous, and the continuity analysis did not show that BMI had a significant effect on the incidence of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Many hospitals have carried out DAA THA and obtained satisfactory postoperative results [14]. With the increase in the number of operations, however, various intraoperative or postoperative complications have emerged [15]. The incidence of femoral fracture ranges from 0.1 to 22.4% [7,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…There are many clinical studies on the relationship between obesity and DAA-THA, they put forward many different viewpoints [28][29][30][31][32][33][34][35]. However, there is still no uni ed conclusion on whether obesity have a negative impact on total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [15,18] reported that patients with obesity and advanced age were not suitable for DAA THA, the risk of complications such as fractures was high. In this study, patients had heterogenic BMIs, and the continuity analysis did not show that BMI had a signi cant effect on the incidence of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Many hospitals have carried out DAA THA and obtained satisfactory postoperative results [14]. With the increase of operations, however, various intraoperative or postoperative complications have emerged [15]. The incidence of femoral fractures varied between 0.1% and 22.4% [7,[16][17].…”
Section: Discussionmentioning
confidence: 99%